Synthetic strategies to nanostructured photocatalysts for CO2 reduction to solar fuels and chemicals. Issue 28 (28th July 2015) - Chen, Donna; Zhang, Xingguang; Lee, Adam F.
<x xml:space="preserve">Abstract</x> Advances in nanomaterials synthesis offer new routes to solar fuels and chemicals from CO2 as a sustainable chemical feedstock.